The Suitability Analysis and Carrying Capacity of Marine Tourism Area (Case Study of Ujung Suso Beach, East Luwu Regency) - Bibin, Muhammad; Mecca, Adiba Nuwaira (Torani Journal of Fisheries and Marine Science, 2020)
The development of Ujung Suso Beach as a marine tourism destination requires knowledge of the condition and existence of existing natural resources. The location of the Ujung Suso beach is far from the provincial / regency capital, so that a large investment is needed and there are still some limitations such as accessibility, and basic facilities and infrastructure. In connection with this condition data it is important for local governments to carry out area management. The suitability of land and the carrying capacity of the area to develop marine tourism absolutely requires the support of correct and science-based data and information. The purpose of this research is to examine the potential of natural resources in the Ujung Suso Beach Tourism Area and to analyze the suitability and carrying capacity of the Ujung Suso Beach Tourism Area. This research is located in the Ujung Suso Beach Tourism Area, East Luwu Regency. This research uses tourism suitability analysis and area carrying capacity analysis. The results of the analysis show that the Ujung Suso Beach Tourism Area is very suitable (S1) for beach tourism activities in the recreation category with a value of 86.66%, for marine tourism activities, the snorkeling and diving categories are included in the appropriate category (S2) with a score of 81.66% and 66.66%. The total value of the carrying capacity of the Ujung Suso Beach Tourism Area is 279 people / day. Based on the perception of tourists that public transportation to get to the Ujung Suso Beach Tourism Area is still lacking.